High- and low-affinity sites for sodium in δ-OR-Gi1α (Cys (351)-Ile (351)) fusion protein stably expressed in HEK293 cells; functional significance and correlation with biophysical state of plasma membrane - Vošahlíková, Miroslava; Jurkiewicz, Piotr; Roubalová, Lenka; Hof, Martin; Svoboda, Petr (Naunyn-Schmiedeberg's archives of pharmacology, 2014)
The effect of sodium, potassium, and lithium on δ-opioid receptor ligand binding parameters and coupling with the cognate G proteins was compared in model HEK293 cell line stably expressing PTX-insensitive δ-OR-Gi1α (Cys(351)-Ile(351)) fusion protein. Agonist [(3)H]DADLE binding was decreased in the order Na(+) ≫ Li(+) > K(+) > (+)NMDG. When plotted as a function of increasing NaCl concentrations, the binding was best-fitted with a two-phase exponential decay considering two Na(+)-responsive sites (r (2) = 0.99). High-affinity Na(+)-sites were characterized by Kd = 7.9 mM and represented 25 % of the basal level determined in the absence of ions. The remaining 75 % represented the low-affinity sites (Kd = 463 mM). Inhibition of [(3)H]DADLE binding by lithium, potassium, and (+)-NMDG proceeded in low-affinity manner only. Surprisingly, the affinity/potency of DADLE-stimulated [(35)S]GTPγS binding was increased in a reverse order: Na(+) < K(+) < Li(+). This result was demonstrated in PTX-treated as well as PTX-untreated cells. Therefore, it is not restricted to Gi1α(Cys(351)-Ile(351)) within the δ-OR-Gi1α fusion protein, but is also valid for stimulation of endogenous G proteins of Gi/Go family in HEK293 cells. Biophysical studies of interaction of ions with polar head-group region of lipids using Laurdan generalized polarization indicated the low-affinity type of interaction only proceeding in the order: Cs(+) < K(+) < Na(+) < Li(+). The results are discussed in terms of interaction of Na(+), K(+) and Li(+) with the high- and low-affinity sites located in water-accessible part of δ-OR binding pocket. We also consider the role of negatively charged Cl(-), Br(-), and I(-) counter anions in inhibition of both [(3)H]DADLE and [(35)S]GTPγS binding.
Keywords: Lipid Bilayers; Recombinant Proteins; vazebná místa; HEK293 buňky; leucin-2-alanin-enkefalin; GTP-Binding Protein alpha Subunits, Gi-Go; lipidové dvojvrstvy; lithium; HEK293 Cells; sodík; Guanosine 5'-O-(3-Thiotriphosphate); Lithium; rekombinantní proteiny; Sodium; Binding Sites; Cell Membrane; lidé; Humans; buněčná membrána; Enkephalin, Leucine-2-Alanine; guanosin 5'-O-(3-thiotrifosfát); Receptors, Opioid, delta; proteiny vázající GTP - alfa-podjednotky Gi-Go; receptory opiátové delta